Two-dimensional molecular networks at the solid/liquid interface and the role of alkyl chains in their building blocks - Liu, Suyi; Norikane, Yasuo; Kikkawa, Yoshihiro (Beilstein Journal of Nanotechnology, 2023)
Nanoarchitectonics has attracted increasing attention owing to its potential applications in nanomachines, nanoelectronics, catalysis, and nanopatterning, which can contribute to overcoming global problems related to energy and environment, among others. However, the fabrication of ordered nanoarchitectures remains a challenge, even in two dimensions. Therefore, a deeper understanding of the self-assembly processes and substantial factors for building ordered structures is critical for tailoring flexible and desirable nanoarchitectures. Scanning tunneling microscopy is a powerful tool for revealing the molecular conformations, arrangements, and orientations of two-dimensional (2D) networks on surfaces. The fabrication of 2D assemblies involves non-covalent interactions that play a significant role in the molecular arrangement and orientation. Among the non-covalent interactions, dispersion interactions that derive from alkyl chain units are believed to be weak. However, alkyl chains play an important role in the adsorption onto substrates, as well as in the in-plane intermolecular interactions. In this review, we focus on the role of alkyl chains in the formation of ordered 2D assemblies at the solid/liquid interface. The alkyl chain effects on the 2D assemblies are introduced together with examples documented in the past decades.
Keywords: alkyl chains; scanning tunneling microscopy; self-assembly; solid/liquid interface; two-dimensional networks